Conical Perspective and Fractal Theory:A Comparative and Contrastive Approach - Daniel Sofron (Anastasis: Research in Medieval Culture and Art)
This paper explores a possible connection between Euclidean geometry, which lies at the basis of conical perspective, and fractal geometry, which could, in turn, generate a new system of spatial representation in art. Founded by Renaissance theorists and artists and applied exclusively to the visual arts as the only method of shaping the pictorial space for nearly five centuries, conical perspective has been increasingly questioned by modern artists. As a system of geometric relationships, conical perspective was based on the principles of Euclidean geometry. The new concepts of non-Euclidean geometry emerging in the second half of the 19th century have led to a change in the artists' perception of space, generating a quest for new ways of spatial representation. In the 1970s, Benoit Mandelbrot theorised a new type of geometry – fractal geometry – which subsequently became a second antiEuclidean revolution that led to an unprecedented positioning of visual artists with regard to the expression of spatiality. From this point of view, fractal geometry can be seen as another system of visual representation of reality, alongside the already established ones.